Political and Geopolitical Risks in Multinational Capital Budgeting: A Systematic Review and Integrated Risk–Strategy Framework - Husnaeda; Irpan; Muchriana Muchran; Muh. Rum (Pustaka Digital Indonesia, 2026)
Cross-border investment decisions by multinational corporations are increasingly shaped by political and geopolitical uncertainties in the global environment. This study aims to examine the concept of multinational capital budgeting, identify key cross-country investment risks, and analyze risk mitigation strategies through a systematic literature review (SLR). A total of 48 peer-reviewed articles published between 2020 and 2025 were analyzed following PRISMA guidelines. The findings reveal five dominant dimensions of risk affecting multinational investment decisions: political risk, geopolitical risk, exchange rate risk, country risk, and economic policy uncertainty. Among the identified strategies, the risk-adjusted discount rate is the most widely applied approach (66.7%), followed by the real options approach (31.3%) and scenario analysis (29.2%). Empirical synthesis indicates that a 1% increase in geopolitical risk index is associated with a 5.79% decline in foreign direct investment (FDI), highlighting the sensitivity of investment flows to global uncertainty. However, political stability and financial development significantly moderate this negative impact, reducing it by up to 60–70%. This study contributes by developing an integrated decision framework that maps risk profiles to appropriate capital budgeting strategies. The findings suggest that no single method is universally optimal; instead, the effectiveness of capital budgeting techniques depends on risk characteristics, institutional quality, and firm capabilities. The study offers both theoretical insights and practical guidance for financial managers and policymakers in navigating investment decisions under uncertainty.